The land and the people : the Wik lectures 1998 - Atkinson, Alan.; Morton, Richard James; History Institute, Victoria (Carlton, Vic. : History Institute, 1998)
Series of lectures looking at the history of land ownership in Australia and the effects on current land rights of Aboriginals; terra nullius; Aboriginal traditional relationship to land; early recognition of Aboriginal ownership of land; Lectures by John Mulvaney, Alan Atkinson, Henry Reynolds, Bill Gammage and Frank Brennan entered separately.
Lectures delivered in the "Land and the people" public lecture series, April-August, 1998.
Keywords: Native title; Aboriginal Australians -- Land tenure -- Government policy; Aboriginal Australians -- Government relations; Land tenure -- Law and legislation -- Australia -- History; Torres Strait Islanders -- Land tenure -- Government policy; Torres Strait Islanders -- Government relations; Land rights - Ownership; Culture - Relationship to land; Land rights; Colonisation; Law - Jurisprudence - Terra nullius; Australia